The Effect of Olive Oil and Tin Leaf Extract on GDP Levels in White Rats - Jannah, Reza Miftahul; Syamsu, Rachmat Faisal; Karim, Marzelina; Julyani, Sry; Kartika, Andy Visi (Jurnal Biologi Tropis, 2024)
Diabetes Mellitus is a chronic condition characterized by fasting blood glucose levels of less than 126 mg/dl, which are above the normal range. DM is otherwise called the quiet executioner since it is frequently not understood and when it is found complexities have happened. Monounsaturated fatty acids (MUFA), which have anti-diabetic properties, can be found in olive oil, a functional food. Fig leaves contain flavonoid compounds, β-setosterol, and these polyphenols are accounted for to work as antidiabetics. The point of this study was to decide the impact of directing olive oil and fig leaf separate on fasting blood glucose levels in white rodents. This study employs a Pretest-Posttest Control Group Design and quantitative experimental research methods. The examples utilized were 24 mice. The independent t-test was used to process the results, and One Way Annova was used to carry on. According to the findings of the study, the group that received olive oil had a fasting blood glucose of 41.00 mg/dL (p0.004), the group that received fig leaf extract had a p value of 37.25 mg/dL (p0.005), and the group that received a mixture of olive oil and fig leaf extract had a p value of 39.00 mg/dL (p0.004). Olive oil and fig leaf extract both have an effect on the blood glucose levels of mice induced by Aloxan, but the combination yields more significant results. This is the study's conclusion.